2020
DOI: 10.1109/tvt.2020.2963847
|View full text |Cite
|
Sign up to set email alerts
|

Fast Beam Training Architecture for Hybrid mmWave Transceivers

Abstract: Millimeter-wave (mmWave) communications attract considerable interest due to the massive available spectrum. However, to establish communication links, a beam training procedure is indispensable. How to accelerate the beam training process is one of the key challenges towards realizing mmWave communications in practice. In this study, we first propose a novel low-cost digital beamforming (DBF) module assisted hybrid (DA-hybrid) architecture, by exploiting both the capabilities of analog and digital modules. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…To accelerate the beam training process, the authors of [30] proposed a low-cost hybrid architecture assisted by a digital beamforming module and designed a fast beam training method by utilizing the proposed architecture and using the sparsity of mmWave channels. To improve the latency performance of mmWave networks for industrial automation, the authors of [31] proposed an adaptive beam selection strategy to select the best set of beams among multiple users to reduce the overall latency for all users.…”
Section: Mmwave Beam Managementmentioning
confidence: 99%
“…To accelerate the beam training process, the authors of [30] proposed a low-cost hybrid architecture assisted by a digital beamforming module and designed a fast beam training method by utilizing the proposed architecture and using the sparsity of mmWave channels. To improve the latency performance of mmWave networks for industrial automation, the authors of [31] proposed an adaptive beam selection strategy to select the best set of beams among multiple users to reduce the overall latency for all users.…”
Section: Mmwave Beam Managementmentioning
confidence: 99%
“…In (13), and are the speed of light and the distance of the path from the vehicle i to the mmSBS, respectively.…”
Section: A Simulation Settingsmentioning
confidence: 99%
“…By analyzing the average search delay of two different mmWave network models, the authors in [12] found that the average number of searches is related to the number of search sectors. The authors in [13] designed a low-cost beamforming module-assisted hybrid architecture and proposed a fast beam training method. The authors in [14] studied the sensitivity of the beam stability selected by the base station.…”
Section: Related Workmentioning
confidence: 99%
“…By contrast. The auxiliary array and the data transmission array used the same frequency band in [5]. The auxiliary array of the base station (BS) was used to transmit omnidirectional wave, and the data transmission array of the mobile station (MS) estimated AoDs of multiple paths by orthogonal matching pursuit (OMP) algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the reciprocity of the two channels is stronger than that between sub-6G and millimeter wave [4]. Compared with the auxiliary array of fully digital architecture adopted in [5], the auxiliary array of our scheme employs a small-scale hybrid structure for less cost consumption.…”
Section: Introductionmentioning
confidence: 99%